Issues on majority and minority communities : An ecological perspective - Norahim, Norazuna (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Language ecology is dynamic and changing. Contact between languages within a community may cause conflict; that is minor and major groups competing for the survival of their languages. Nonetheless, smaller ethnolinguistic groups are shown to have survived in a less hostile environment consisting of many larger surrounding languages (e.g. languages of the coastal communities in Papua New Guinea, or Wik languages in Nothern Australia as cited in Mulhausler, 1977). This paper takes the ecological perspective to examine the relationships between majority and minority communities in various sociolinguistic settings. It discusses how an equitable form of balance in an ecolinguistic system is managed, and how it can be in an unbalanced state where "lesser communities" are situated in a disadvantage position, and the survival of their languages threatened. Central to this issue is the notion of group identity, and its link to language and culture. This relationship is built upon societal perceptions of communities and their languages, which in turn influence language behaviour of majority and minority communities.